Collaborative Governance In The Development Of Super Priority Tourism Destinations (DPSP) Likupang, North Minahasa Regency, North Sulawesi Province - Praysilia Janet Lumentah; Mansyur Achmad; Tjahyo Suprayogo (Sean Institute, 2024)
This research departs from the development of the Likupang Super Priority Tourism Destination (DPSP) and the actions taken towards this through collaboration between stakeholders. This research uses the collaborative governance theory from Ansel and Gash (2007). The method in this research uses an exploratory qualitative approach, with the researcher as the research instrument, data collection techniques using interviews, documentation and observation, purposive sampling and snowball sampling techniques for selecting informants, data analysis is carried out by processing and preparing data, reading all the data, coding all data, apply the coding process, present it in the form of a narrative/qualitative report and interpret the data. The research results show that Collaborative Governance in the Development of Super Priority Tourism Destinations (DPSP) Likupang, North Minahasa Regency has not gone well based on the research approach carried out through Collaborative Governance theory Ansell & Gash (2008) this can be seen in the Strarting Condition in the dimension of resource imbalance, be it human resources, availability of financial resources or supporting infrastructure. Furthermore, seen from the Institutional Design dimension, all collaborating actors carry out their respective functions in accordance with their functions without any guidelines or specified time periods, all of which run conditionally. In the Collaborative Process Dimension, namely Face to Face, there is still a weakening of mutual understanding between collaborative actors due to the lack of space and time, implementation is not routine and adapts to the situation and conditions that occur and has an impact on differences in interests that are difficult to reconcile. Analyzing the inhibiting factors and efforts to overcome collaborative governance obstacles in the development of the Likupang Super Priority Tourism Destination (DPSP).